Comparative study on some properties of polyphosphatasephosphohydrolase in Neurospora crassa strain ad-6 (28610) a and a leaky derivative. - L. V. Trilisenko; V. M. Vagabov; I. S. Kulaev (Fungal Genetics Reports, 1982)
Comparative study on some properties of polyphosphatasephosphohydrolase in Neurospora crassa strain ad-6 (28610) 5 and a leaky derivative.